A Report from South Korea: What elementary school teachers want to teach and what they teach in the history class: The Korean case. Issue 1 (1st August 2011) - Kang, Sunjoo
Abstract : This paper explores the views of five Korean elementary teachers on the purposes of teaching Korean history by analyzing their interview responses and observation of their classroom instruction. It is important to understand how teachers define the purpose of history teaching because it influences on students' constructing their view on the past, present as well as future. Six viewpoints are identified: history as a source of national identity and patriotism, history as achievement of greatness, history as morality, history as an aid in resolving contemporary issues, history as an approach to knowledge, and history as an aid to expand human beings' self-knowledge. The types and nature of the rationales provided by the teachers and a comparison of the teachers' interview responses with their classroom practices and with the guidelines in the Korean National curriculum is also discussed.